Influenza: state-of-the-art and vaccination during COVID-19 pandemic - Editorial Article (Лечащий Врач)
Despite the COVID-19 pandemic, seasonal infections, in particular the influenza virus, are still in our reality. We have discussed with Dmitry Lioznov, the acting head of Smorodintsev Research Institute of Influenza, how the pandemic has changed the influenza vaccination rates and state-of-the-art in of influenza diagnostic and therapeutic approaches.